2021
DOI: 10.1007/s00262-020-02834-y
|View full text |Cite
|
Sign up to set email alerts
|

A template to quantify the location and density of CD3 + and CD8 + tumor-infiltrating lymphocytes in colon cancer by digital pathology on whole slides for an objective, standardized immune score assessment

Abstract: Background In colon cancer, the location and density of tumor-infiltrating lymphocytes (TILs) can classify patients into low and high-risk groups for prognostication. While a commercially available ‘Immunoscore®’ exists, the incurred expenses and copyrights may prevent universal use. The aim of this study was to develop a robust and objective quantification method of TILs in colon cancer. Methods A consecutive, unselected series of specimens from patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 38 publications
(47 reference statements)
0
8
1
Order By: Relevance
“…Mean values of CD3+ and CD8+ lymphocytes in our study were high compared to some analyses; however, even higher mean densities of lymphocytes, especially in early stages of the disease, and higher intrapatient variability of the density of lymphocytes have been reported [10][11][12][13]. In most studies, only semi-quantitative evaluations of TIL densities were conducted, making it difficult to perform conclusive comparisons in this regard.…”
Section: Discussioncontrasting
confidence: 73%
“…Mean values of CD3+ and CD8+ lymphocytes in our study were high compared to some analyses; however, even higher mean densities of lymphocytes, especially in early stages of the disease, and higher intrapatient variability of the density of lymphocytes have been reported [10][11][12][13]. In most studies, only semi-quantitative evaluations of TIL densities were conducted, making it difficult to perform conclusive comparisons in this regard.…”
Section: Discussioncontrasting
confidence: 73%
“…T cells play one of main roles in a tumour invasion. Lea et al reported very similar results: Perineural invasion was associated with a low Immunoscore (p = 0.008), but lymphatic invasion had no significant association with its changes (p = 0.10)(Lea et al, 2021). These results could indicate the potential role of CD8+ T cells in tumour metastasis potential and local structure involvement, as well as local tumour growth.…”
mentioning
confidence: 78%
“…lymphocytes are known to limit neoplastic cell growth, to suppress tumour infiltration, and to induce elimination of tumours(Steele et al, 2018). In CRC, the presence of CD8+ lymphocytes is associated with high MSI, although data about overall survival is controversial(Lea et al, 2021;Millen et al, 2020;Sudoyo et al, 2019). A high CD8+ T cell count has been associated with stage I-II CRC (p = 0.017), and the CD8+ T cell count is significantly higher in the tumour centre and invasive margin in MSI tumours compared with MSS tumours(Lea et al, 2021).Researchers have also suggested that a combined score of CD8+ T cells and tumour buds in CRC could be a better prediction marker for nodal metastases and survival(Dawson et al., transmembrane glycoprotein that normally participates in cell-cell interactions, adhesion of the cytoskeleton to the extracellular matrix, and cell migration.…”
mentioning
confidence: 99%
See 2 more Smart Citations